PENGARUH PELATIHAN BEBAN LEG PRESS TERHADAP KECEPATAN LARI DAN DAYA LEDAK OTOT TUNGKAI - Mahayasa Hadiwijaya, Made (Universitas Pendidikan Ganesha, 2013)
The aim of this study to determine the effect of weight training on leg press towards running speed and explosive power leg muscle. Type of this research is real experimental (true experimental) with draft of The Randomized Pretest-Posttest Control Group Design. 60 samples from class X of SMK Negeri 1 Singaraja school year 2012/2013 are determined by random sampling technique. Running speed was measured with a 50 meters sprint test and leg muscle explosive power measured by the vertical jump test, then the data were analyzed by independent t-test at significance level (α) of 0.05. Calculated significance value smaller than the value of α (0.05), thus the research hypothesis